نشأة اللغة العربية وتطورها فى التاريخ الإسلامي - Darwin Zainuddin (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2022)
Arabic is a language that contributes vocabulary to languages that exist in the world, the main reason is that this language is used in the holy book, namely al-Qur'an which has survived in its original language for more than 14 centuries. Arabic is one of the Samiyah language families, ascribed to the son of the Prophet Noah named Sam ibn Nuh, then Arabic moved to "Ya'rab ibn Qahthan" to Prophet Ibrahim who used Arabic so that Arabic developed to the land of the Hijaz, Nejed, and surroundings. As for the inscription about Baidah Arabic which is estimated to have lived in the 1st century BC, which uses three dialects, namely Tsyamudiyah, Syafwiyah, and Lihyaniyah. Meanwhile, Baqiyah Arabic was discovered after the 5th century AD, which is used by Arabs in literature, writing, and essay. The Arabic dialect of Bagiyah has two families, namely the western side of the Hijaz which uses the dialect of "Quraish", and the eastern side of Nejed is "Tamimiyah". These two dialects developed the Arabic Fusha language which became the language of the Qur'an and Hadith.